2009
DOI: 10.1038/ja.2008.26
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial activity of ciprofloxacin and norfloxacin permanently bonded to polyethylene glycol by a thiourea linker

Abstract: C 2 -symmetric (divalent) biologically active molecules are an extensively studied field, as certain substances possessing a B-linker-B type structure (where B represents a bioactive molecule) have promising biological properties. 1 The synthesis and investigation of the dimers of the highly antibacterial quinolonecarboxylic acids were also carried out. However, the norfloxacin dimers linked with an alkyl chain, described by Coppel et al., 2 were very slightly active. Later Kerns et al. 3-5 synthesized the C 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Indeed, transport through porin channels is considered a complex function of physicochemical properties (e.g., molecular weight, conformation, hydrophilicity, and charge) of the translocating molecules . Until now, many studies have reported that OmpF permitted transport of ciprofloxacin tailed with various hydrophilic, thread-like nonelectrolytes (e.g., polyethylene glycol, poly­(2-methyloxazoline), and poly­(2-ethyloxazoline)) that possessed a molecular weight ranging from 1382 to more than 3000. These observations, including the one herein, all seemed in contradiction with the established exclusion limit of OmpF, but reasonable, because these nonelectrolyte “tails” differed from saccharides in conformation. However, when the “tail” in Cipro-PNIPAM 23 deformed into a bulky globule at 33 °C, the conjugate would get stuck at the narrow opening of the porins, excluding the drug “head” from accessing intracellular targets.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Indeed, transport through porin channels is considered a complex function of physicochemical properties (e.g., molecular weight, conformation, hydrophilicity, and charge) of the translocating molecules . Until now, many studies have reported that OmpF permitted transport of ciprofloxacin tailed with various hydrophilic, thread-like nonelectrolytes (e.g., polyethylene glycol, poly­(2-methyloxazoline), and poly­(2-ethyloxazoline)) that possessed a molecular weight ranging from 1382 to more than 3000. These observations, including the one herein, all seemed in contradiction with the established exclusion limit of OmpF, but reasonable, because these nonelectrolyte “tails” differed from saccharides in conformation. However, when the “tail” in Cipro-PNIPAM 23 deformed into a bulky globule at 33 °C, the conjugate would get stuck at the narrow opening of the porins, excluding the drug “head” from accessing intracellular targets.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, PEG is a non-toxic polymer with having amphiphilic nature, as it can dissolve into both water and organic solvents. Biologically active materials when linked to PEG, can have enhanced properties of pharmacodynamics because of the amphiphilic nature of PEG (Pintér et al 2009). Surface modification with PEG-like PEGylated conjugates provides better stability, enhanced controlled release, low immunogenic response, and prolonged systemic circulation time (Ghitman et al 2018).…”
Section: Anti-biofilm Assaymentioning
confidence: 99%
“…Polymer–drug conjugates are arguably the commonest forms of polymer therapeutics and, like other polymer therapeutic subclasses, have properties substantially distinct from the conventional alternatives (Table ). Additionally, conjugation creates new, original macromolecules, affording intellectual property space, which is crucial for successful commercialisation (Pinter, Horvath, Bujdoso, et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%